2018
DOI: 10.3390/genes9010027
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Evolutionary Relationships in the Giant Sex Chromosomes of Three Microtus Species

Abstract: The genus Microtus has high karyotypic diversity. The existence of notable differences in the length of its sex chromosomes contributes to this variation. Variations in size are attributed to the enlargement of their heterochromatin content, which is of such magnitude in some species that they are referred to as “giant sex chromosomes”. Here, we perform an intra- and interspecific analysis of the molecular composition of the heterochromatic blocks in three species with giant sex chromosomes (Microtus chrotorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Ostensibly, M. cabrerae and M. agrestis share certain unusual genetic features, including the presence of giant sex chromosomes, which could be regarded as additional proof of their phylogenetic proximity. However, several studies have clearly demonstrated that these enlarged sex chromosomes arose and evolved independently in the genus Microtus [ 4 ], and hence, their presence is not a robust criterion for the inclusion of M. cabrerae and M. agrestis in the same subgenus. A previous mitochondrial phylogenetic reconstruction obtained similar results, with M. cabrerae and M. agrestis clustered in the same clade, but the level of genetic divergence indicated that both species could be considered as members of two different subgenera ( Agricola and Iberomys ) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ostensibly, M. cabrerae and M. agrestis share certain unusual genetic features, including the presence of giant sex chromosomes, which could be regarded as additional proof of their phylogenetic proximity. However, several studies have clearly demonstrated that these enlarged sex chromosomes arose and evolved independently in the genus Microtus [ 4 ], and hence, their presence is not a robust criterion for the inclusion of M. cabrerae and M. agrestis in the same subgenus. A previous mitochondrial phylogenetic reconstruction obtained similar results, with M. cabrerae and M. agrestis clustered in the same clade, but the level of genetic divergence indicated that both species could be considered as members of two different subgenera ( Agricola and Iberomys ) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…A single male specimen of M. cabrerae (Siles, Spain (TOPC-0902)) and one of M. thomasi (Edessa, Greece, (R231)) were used for DNA extraction, while for M. chrotorrhinus (North America), an established cell line from a male individual was employed [ 4 , 40 ]. All capture and sacrifice protocols were approved by the Junta de Andalucía Ethics Committee for Animal Experimentation (code: 04/09/2018/130).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Karyotype evolution encompassed a series of fusion/fission rearrangements, inversions, and centromeric shifts, accompanied by other cryptic intrachromosomal rearrangements [6,7], leading to extensive variability in chromosome numbers ranging from 2n = 17 in Ellobius lutescens to 2n = 62 in M. duodecimcostatus and M. lusitanicus [8,9]. Some species from the genus Microtus are characterized by atypical sex-related genetic features that range from an unusual sex determination system to extensive sex chromosome polymorphisms [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. In the genus Microtus, a numerous collection of variants evolved from an ancestral sex chromosome pair, even within related species or at intraspecific level [8,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%